Responsibility loadings for dental services by general dentists - Spencer A John; Brennan David S (BMC, 2010)
Abstract Background Responsibility loadings determine relative value units of dental services that translate services into a common scale of work effort. The aims of this paper were to elicit responsibility loadings for a subset of dental services and to relate responsibility loadings to ratings of importance of the components of responsibility. Methods Responsibility loadings and ratings of components of responsibility were collected using mailed questionnaires from a random sample of Australian private general practice dentists in 2007 (response rate = 77%). Results Median responsibility loadings were 1.25 for an initial oral examination and for a 3+-surface amalgam restoration, 1.50 for a simple extraction and for root canal obturation (single canal), and 1.75 for subgingival curettage (per quadrant). Across the five services coefficients from a multivariate logit model showed that ratings of importance of knowledge (0.34), dexterity (0.24), physical effort (0.28) and mental effort (0.48) were associated with responsibility loadings (P < 0.05). Conclusions The elicited median responsibility loadings showed agreement with previous estimates indicating convergent validity. Components of responsibility were associated with loadings indicating that components can explain and predict responsibility aspects of dental service provision.